M-Breather, Lumps, and Soliton Molecules for the 2+1-Dimensional Elliptic Toda Equation - Yuechen Jia; Yu Lu; Miao Yu; Hasi Gegen (Advances in Mathematical Physics)
The 2+1-dimensional elliptic Toda equation is a higher dimensional generalization of the Toda lattice and also a discrete version of the Kadomtsev-Petviashvili-1 (KP1) equation. In this paper, we derive the M-breather solution in the determinant form for the 2+1-dimensional elliptic Toda equation via Bäcklund transformation and nonlinear superposition formulae. The lump solutions of the 2+1-dimensional elliptic Toda equation are derived from the breather solutions through the degeneration process. Hybrid solutions composed of two line solitons and one breather/lump are constructed. By introducing the velocity resonance to the N-soliton solution, it is found that the 2+1-dimensional elliptic Toda equation possesses line soliton molecules, breather-soliton molecules, and breather molecules. Based on the N-soliton solution, we also demonstrate the interactions between a soliton/breather-soliton molecule and a lump and the interaction between a soliton molecule and a breather. It is interesting to find that the KP1 equation does not possess a line soliton molecule, but its discrete version—the 2+1-dimensional elliptic Toda equation—exhibits line soliton molecules.